PERSEPSI MAHASISWA TERHADAP SALES PROMOTION GIRL DI KOTA PEKANBARU - Ninik Priscilla; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
How they wearing dress which categorized as sexy (short), striking facial makeup, often met in the night for promoting or selling the product to the consumers and the graceful attitude of some cigarettes sales promotion girl when trying to attract the attention of consumers make a negative perceptions of this profession . Cigarettes Sales promotion girl values only rely on the elegance of the body and the face. The aims of study are to determine the factors affected student perceptions of cigarettes sales promotion girl at the city of Pekanbaru and the process of forming student perceptions of cigarettes sales promotion girl at the city of Pekanbaru.This study uses descriptive data analysis with qualitative research and taking informants by using five accidental sampling. With the participant data collection techniques, in-depth interviews and documentation. As for the technique to checking the validity of the data, the researcher uses the extension technique of participation. The obtained data are then processed for reduction, presented until a general conclusion is produced.The results of this study indicate that the factors affected the perception of students to cigarettes sales promotion girl at the city of Pekanbaru is (a) the object perceived, which depends on each individual looking in the different side where and how to responds to their existence. They are seem like that because the demands of working not of their own accord, (b) attention, not apart from the beautiful face, soft tone, easy to smile, how to look by using clothes which categorized as sexy (like skirt above the knees and as well as short sleeves) and Proficient in dressing up. The process of establishing the student perception of cigarettes sales promotion girl at Pekanbaru city is (a) registration where the cigarettes sales promotion girl are selling the cigarettes and matches according to the product they offered with relatively cheap price, (b) the interpretation where the students get the better understanding in detail about the product offered by them and unrarely of them buy and trying the cigarettes products.Keywords: Perception, Student, Cigarettes Sales Promotion Gi